Capturing Key Energy and Emission Trends in CGE Models: Assessment of Status and Remaining Challenges - Taran Faehn; Gabriel Bachner; Robert Beach; Jean Chateau; Shinichiro Fujimori; Madanmohan Ghosh; Meriem Hamdi-Cherif; Elisa Lanzi; Sergey Paltsev; Toon Vandyck; Bruno Cunha; Rafael Garaffa; et al. (Center for Economic Studies and ifo Institute (CESifo), 2020)
Limiting global warming in line with the goals in the Paris Agreement will require substantial technological and behavioural transformations. This challenge drives many of the current modelling trends. This paper undertakes a review of 17 state-of-the-art recursive-dynamic computable general equilibrium (CGE) models and assesses the key methodologies and applied modules they use for representing sectoral energy and emission characteristics and dynamics. The purpose is to provide technical insight into recent advances in the modelling of current and future energy and abatement technologies and how they can be used to make baseline projections and scenarios 20-80 years ahead. In order to represent likely energy system transitions in the decades to come, modern CGE tools have learned from bottom-up studies. We distinguish between three different approaches to baseline quantification: (a) exploiting bottom-up model characteristics to endogenize responses of technology investment and utilization, (b) relying on external information sources to feed the exogenous parameters and variables of the model, and (c) linking the model with more technology-rich, partial models to obtain bottom-up- and pathway-consistent parameters.
Keywords: C68; O13; O14; O18; Q43; Q54; 330; computable general equilibrium models; long-term economic projections; energy; technology change; emissions; greenhouse gases